PENGARUH FAKTOR PSIKOLOGIS, PERSONAL, DAN SOSIAL TERHADAP KEPUTUSAN PEMBELIAN SAMSUNG SMARTPHONE DI RW 01 PONDOK PINANG JAKARTA SELATAN - Irma Indriaryanti Hayuningrum; Lina Aryani (Fakultas Ekonomi dan Bisnis, Universitas Pembangunan Nasional Veteran Jakarta, 2015)
Smartphone is a mobile phone equipped with internet features that allow users to access a veriety of information quickly. Samsung is one company which also issued a smartphone with a variety of types. This study was conducted to examine the relationship between consumer behavior that psychological factors, personal and social skills that encourage consumers to make purchasing decisions. Psychological influenced by motivation, perception, learning, and beliefs. Personal factors or personally affected by the cycle of life, lifestyle, state of the economy. Social influenced by the reference group, the family, the role and status. There are five stages in making purchasing decisions, problem recognition, information search, evaluation of alternatives, purchase decision, and post-purchase behavior. This study aims to determine the effect of partial and simultaneous influence of psychological factors, personal, and social on purchasing decisions. Data collection techniques using primary data by spreading questionnaires to 100 respondents. The sampling technique in this research is Non-Probability Sampling with purposive sampling method. Mechanical analysis using multiple regression analysis. The results of the study simultaneously and partially psychological factors, personal, and social positive and significant impact on purchasing decisions.